Spatial Description of the Distribution Cases of BTA Positive Pulmonary TB in Kota Kupang - Rofina Lidae Lokang Leu; Afrona E. L. Takaeb; Sigit Purnawan (Lontar : Journal of Community Health, 2020)
Tuberculosis is one of the top 10 leading causes of death in the world. In 2017 an estimated 10.4 million people suffered from TB and 1.3 million people died of the disease. TB is a disease based on the region that has a spatial dependence (correlation between geographic regions), therefore its restraint must also consider the spatial distribution patterns of the case that can be learned through spatial analysis. The purpose of this research was to analyze spatially the distribution of BTA positive pulmonary TB cases based on population density, coverage of healthy houses, altitude, and the number of poor families in Kota Kupang 2018. The type of research used in this study was quantitative descriptive with Geographic Information System (GIS) approach. The sample in this study consisted of all new cases of BTA positive pulmonary TB in 2018 amounted to 451 cases. Spatial analysis showed that the BTA positive pulmonary TB cases distributed to spread the subdistricts in Kota Kupang which was a region of low altitude (<150 masl) with the highest distribution in the areas with high population density, high coverage of the healthy house, and the high number of poor families. It calls for networking between the government and the community in the prevention of BTA positive pulmonary TB.